Dynamic response and collapse resistance of RC flat plate structures subjected to instantaneous removal of an interior column. (1st August 2022) - Yang, Zhi; Li, Yi; Guan, Hong; Diao, Mengzhu; Gilbert, Benoit P.; Sun, Hailin; Xu, Lianwu
Highlights: Conduct sudden column removal tests on an RC flat plate substructure under three levels of additional gravity loads. Develop a high-fidelity 3D FEM model of the flat plate substructure specimen. Identify dynamic responses and corresponding load resisting mechanisms of the specimen in the flexural, punching and post-punching stages. Evaluate the dynamic increase factors of the substructure during the entire structural collapse. Abstract: Through quasi-static loading regimes, notable research efforts have been made in recent years towards understanding the structural behaviour and resistance mechanism of reinforced concrete (RC) flat plate structures against progressive collapse events. Nevertheless, dynamic responses, being an inherent nature of any progressive collapse, were unable to be adequately studied in these quasi-static studies. Moreover, fewer studies were performed on flat plate structures under dynamic loading conditions, especially their behaviours under large deformations, i.e., the post-punching stages. To fill this research gap, this paper presents three sequential dynamic tests performed on a 1/3-scaled 2 × 2-bay RC flat plate substructure specimen by instantaneously removing the interior column under three levels of additional gravity loads. In these tests, the substructure specimen was able to withstand the gravity loads up to 2.08 times the load capacities recommended by the DoD and GSA guidelines for nonlinear dynamic analyses. The dynamic responses of the specimen in the flexural, punching and post-punching stages were examined in detail. In addition, a high-fidelity finite element model was developed and validated by the experimental test results. The validated numerical model was subsequently used to quantify the dynamic load redistribution patterns, and the influences of two loading considerations (i.e., loading on the slab overhangs and load release time) on the dynamic responses were also investigated. Finally, the dynamic load increase effects were evaluated based on the analysis model results. The obtained load-based dynamic increase factors (DIFs) of the specimen under different gravity loads were between 1.11 and 1.46 in the pre-punching (flexural) stage, whereas they were no more than 1.06 in the post-punching stage.